TECHNICAL AND ECONOMIC ANALYSIS OF THE USE OF VAPOUR LINE JUICE HEATER (VLJH) AT PURIFICATION STATION (CASE STUDY OF PRADJEKAN SUGAR FACTORY) - Wulandari, Fitri; Kuswardhani, Nita; Rusdianto, Andrew Setiawan (Jurnal Penelitian Sains dan Teknologi Indonesia, 2024)
One of the sugar factories operated by a State-Owned Enterprise (BUMN) is Pradjekan Sugar Factory, which is part of PT Sinergi Gula Nusantara (PT SGN) which is located in Bondowoso Regency, East Java. PG Pradjekan is known as an industry that supplies its own energy which comes from the by-product of sugar cane milling in the form of bagasse at the Boiler Station. The sugar production process requires a very large amount of steam so efficiency is needed in the use of this steam. The aim of this research is to streamline the use of steam using the Vapor Line Juice Heater (VLJH) at the Purification Station and calculate the economic value of fuel savings used by using the Vapor Line Juice Heater (VLJH). The results of the technical analysis of the use of VLJH at the Refining Station show that the use of VLJH can reduce the use of steam by 2.49 tonnes/hour or equivalent to the use of 341.10 tonnes of bagasse worth IDR 170,547,765 for 120 days. The investment was evaluated using the Payback Period (PP), Internal Rate of Return (IRR), and Net Present Value (NPV) techniques. The analysis revealed that the value of IDR 441,981,119 for the NPV > 0. Additionally, IRR value of 53.98% > 12% was calculated, indicating that the installation of VLJH yielded a higher rate of return on investment than the highest interest rate assumption. The PP value was calculated for 1.47 years based on the 8-year economic life of the VLJH.